Social Risk Profile and Cardiovascular‐Kidney‐Metabolic Syndrome in US Adults - Jingkuo Li; Lubi Lei; Wei Wang; Wenbo Ding; Yanwu Yu; Boxuan Pu; Yue Peng; Yinchu Li; Lihua Zhang; Yuanlin Guo (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Poor cardiovascular‐kidney‐metabolic (CKM) health is associated with premature mortality and excess morbidity in the United States. Adverse social conditions have a prominent impact on cardiometabolic diseases during the life course. We aim to examine the association between social risk profile (SRP) and CKM multimorbidity among US adults. Methods and Results We used data from the National Health and Nutrition Examination Survey from 1999 to 2018. The definition of CKM syndrome is the coexistence of subclinical or clinical cardiovascular disease, chronic kidney disease, and metabolic disorders. We classified participants by 4 CKM stages according to the different clinical severity of different forms of CKM syndrome. We calculated the summed number of positive SRP measures, including employed, high‐income level, food secure, high education attainment, private insurance, owning a house, and married, as SRP scores and classified them into 4 levels by quartiles: low (0–2), lower‐middle (3–4), upper‐middle (5–6), and high (7–8). A total of 18 373 US adults, aged 20 to 79 years, were included in our analyses. There were 2567 (9.4%) participants with low SRP score level. Most individual SRP measures and a combined SRP score were associated with CKM stages. Compared with high SRP score level, low SRP level was associated with higher odds of having CKM stage 1 (odds ratio [OR], 1.34 [95% CI, 1.06–1.70]), CKM stage 2 (OR, 2.03 [95% CI, 1.59–2.58]), CKM stage 3 (OR, 5.28 [95% CI, 3.29–8.47]), and CKM stage 4 (OR, 5.97 [95% CI, 4.20–8.49]). Conclusions Cumulative social disadvantage, denoted by higher SRP burden, was associated with higher odds of CKM multimorbidity, independent of demographic and lifestyle factors.